Understanding and Responding to the Terrorism Phenomenon : a Multi-dimensional Perspective. - Nikbay, O. (NATO Science for Peace and Security Series: Human and Societal Dynamics, v. 21., 2007)
Since terrorism is a global issue, counter-terrorism studies are also a global issue which requires cooperation and collaboration of multi-dimensional groups. This publication includes the researches, experiences and perceptions of different parts of this cooperation and collaboration.